2017
DOI: 10.1042/bsr20160517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-338 on morphine tolerance by targeting CXCR4 in a rat model of bone cancer pain

Abstract: The present study aimed to investigate the effects of miR-338 on morphine tolerance through the targeting of CXC chemokine receptor-4 (CXCR4) in a rat model of bone cancer pain (BCP). Sprague–Dawley (SD) rats were obtained and divided into model saline (n=10), model morphine (n=50), normal saline (n=10) and normal morphine (healthy rats, n=10) groups. After BCP rat model establishment, the remaining SD rats (n=40) in the model saline group were assigned into pLV-THM-miR-338, pLV-THM-anti-miR-338, CXCR4 shRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The negative plates were developed with a developing agent (CAS item 7757‐83‐7; Hefei Jiankun Chemical Co, Ltd, Hefei, China). The degree of bone destruction induced by tumor was evaluated . Experiments of each group were repeated in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The negative plates were developed with a developing agent (CAS item 7757‐83‐7; Hefei Jiankun Chemical Co, Ltd, Hefei, China). The degree of bone destruction induced by tumor was evaluated . Experiments of each group were repeated in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, miR-365 could reverse morphine tolerance via inhibiting b-arrestin 2 expression in the spinal cord; 8 miR-375 could signicantly hinder morphine tolerance via inhibiting JAK2/STAT3 pathway; 28 miR-93 may be involved in the tolerance by targeting Smad5; 29 miR-338 could suppress the tolerance by targeting CXCR4. 30 In our study, we found that miR-26b was decreased during the morphine tolerance, and miR-26b-mimic could attenuate the tolerance signicantly.…”
Section: Discussionmentioning
confidence: 52%
“…Morphine tolerance was remarkably suppressed in pLV-THM-miR-338 rats with lower expression of CXC chemokine receptor-4 (CXCR4). Although the specific mechanisms of miR-338 targeting of CXCR4 was unknown, miR-338 significantly influenced the inhibition of morphine tolerance (Mei et al, 2017 ).…”
Section: Relevance Of Mirna-based Mechanisms In Morphine Tolerancementioning
confidence: 99%